Border policing, procedural justice and belonging: the legitimacy of (cr)immigration controls in border areas - Brouwer, Jelmer (The British journal of criminology, 2018)
Research suggests that social identity plays an important role in citizens’ views of legal authorities. This article draws on fieldwork observations and semi-structured interviews or surveys to examine both officers’ perceptions and the experiences of people that are stopped in the context of border policing in the border areas of the Netherlands. Our results indicate that non-Dutch citizens and Dutch majority group members generally find these stops acceptable, while Dutch ethnic minority group members perceive them as more problematic. This was mostly related to the feeling of being profiled and a lack of clarity about the reason for the stop. While officers were committed to fair treatment, they also believed that the impact of a stop is very limited. The article finishes by discussing the implications of these findings for issues of belonging and legitimacy. The article finishes by discussing the implications of these findings for issues of belonging and legitimacy.